Chemical composition and growth performance ofbroilers fed small particle size of palm kernel cake - Shakirin, Faridah Hanim; Abdullah, Norhani; Liang, Juan Boo; Mohamed Mustapha, Noordin (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2015)
Palm kernel cake (PKC) is the residue left after oil extraction of the palm kernel. Some chemical components like crude protein, fat, fibre, starch and mineral content can be affected by the particle sizes of the feed. Hence, PKC was subjected to particle size separation by using sieves with nominal apertures of 8.00, 4.75, 2.80, 2.00, 0.50, 1.00, 0.30, 0.50 and 0.30mm. The results showed that particle size of 0.15mm was the major component in PKC (20.9 ± 0.88%), followed by particle size of 1.5mm (15.0 ± 0.14%), and 0.75mm (12.9 ± 0.31%). The small particle size 0.15-1.5mm made up 58% of PKC. Particle size 0.15-0.75mm showed higher protein and crude fat, but lower crude fibre, NDF and ADF when compared to the un-sieved PKC. Sieved PKC (< 1.5mm) was used in a growth performance study with broilers in a 2×3 factorial experiment in a completely randomized design with one control diet. The first factor was two types of PKC (un-sieved and sieved) and the second factor consisted of un-sieved PKC or sieved PKC (SPKC) at 10, 20, and 30% in the rations. Addition of 10% and 20% of un-sieved PKC and SPKC did not show any significant difference in weight gained and feed conversion ratio when compared to the control birds. However, addition of 30% un-sieved PKC or SPKC significantly (P<0.05) reduced body weight gained and increased the feed conversion ratio. There was no significant effect of SPKC on growth performance of broilers when compared to un-sieved PKC.